Test Case Generation for Arduino Programming Instructions using Functional Block Diagrams - Padmanabhan, Mani (Trends in Sciences, 2022)
Interconnecting different wireless sensor and actuator network in the real-time systems are more demanding for testing. High capability is needed to enable efficient methodologies for testing. The major source of effective testing is the identification of test cases. Programming instruction based test case generation has not well suitable for Arduino real-time systems, that an open statement in the research community. This paper introduces a functional block diagram based test case generation framework to facilitate the functional evaluation of Arduino real-time systems. It makes from the functional block diagram. First, block diagrams are converted to the Event Sequence Graph, then the event node is minimized, the test cases are generated minimized event. The presented methodology has validated with the Arduino programming language. This proposed approach quantified with five sensors based Arduino real-time system experiments shows that based on the validated test cases; the development time and cost of the Arduino real-time systems have dynamically reduced. HIGHLIGHTS Software testing results ensure the quality of the developed software. Programming instruction based testing has not well suitable for Arduino real-time systems Arduino functional block diagrams are converted to the event node for test case generation. Event Sequence Graph conversion algorithm provide the event direction Validation of Arduino software programming based on Arduino functional block diagrams identify the new fault detection capability GRAPHICAL ABSTRACT